2014
DOI: 10.1097/mpg.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

PedsQL Gastrointestinal Symptoms Module

Abstract: Objective: The objective of this study was to report on the measurement properties of the Pediatric Quality of Life Inventory (PedsQL) Gastrointestinal Symptoms Module for patients with functional gastrointestinal (GI) disorders (FGIDs) and organic GI diseases, hereafter referred to as ''GI disorders,'' for patient self-report ages between 5 and 18 and parent proxyreport for ages between 2 and 18 years. Methods: The 74-item PedsQL GI Module and 23-item PedsQL Generic Core Scales were completed in a 9-site stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 50 publications
2
78
0
Order By: Relevance
“…Perhaps, as suggested by De Los Reyes [21], some treatments may demonstrate better child outcomes when assessed by child self-report (e.g., cognitive behavior therapy for anxiety [internalizing symptoms] disorders in which the child is the focus of the intervention), and some treatments may demonstrate better child outcomes when assessed by parent proxy-report (e.g., behavioral parent training for conduct disorders (externalizing symptoms) in which the parent is the focus of the intervention). Finally, some treatments may demonstrate better child health outcomes when both the child and parent agree on the presence and severity of the symptoms (e.g., gastrointestinal symptoms in which both the child and parent agree [36], and concur that the symptoms warrant pharmaceutical and/or dietary intervention which may potentially enhance their joint adherence to the treatment regimen). Notably, prior research in children with emotional and behavioral problems referred to mental health clinics found that only 63 % of parent–child dyads agreed on the presence of even a single symptom or problem, with higher agreement on externalizing rather than internalizing symptoms or problems [37].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, as suggested by De Los Reyes [21], some treatments may demonstrate better child outcomes when assessed by child self-report (e.g., cognitive behavior therapy for anxiety [internalizing symptoms] disorders in which the child is the focus of the intervention), and some treatments may demonstrate better child outcomes when assessed by parent proxy-report (e.g., behavioral parent training for conduct disorders (externalizing symptoms) in which the parent is the focus of the intervention). Finally, some treatments may demonstrate better child health outcomes when both the child and parent agree on the presence and severity of the symptoms (e.g., gastrointestinal symptoms in which both the child and parent agree [36], and concur that the symptoms warrant pharmaceutical and/or dietary intervention which may potentially enhance their joint adherence to the treatment regimen). Notably, prior research in children with emotional and behavioral problems referred to mental health clinics found that only 63 % of parent–child dyads agreed on the presence of even a single symptom or problem, with higher agreement on externalizing rather than internalizing symptoms or problems [37].…”
Section: Discussionmentioning
confidence: 99%
“…The PedsQL GI Module (10) is also available to measure baseline GI-specific quality of life and could be used to assess changes in health status over time. These scales contribute to research and clinical practice by measuring changes on a broad spectrum of GI symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the increasing importance of patient-reported outcomes (PROs) which integrate the patient’s perspective and the critical perspectives of parents into the assessment and treatment of patients (910), we developed child and parent report versions of the screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic gastroesophageal reflux is evaluated at 6 weeks, 12 weeks, 5 months and 1 year using the Infant Gastroesophageal Reflux Questionnaire Revised [31]. Gastrointestinal problems are measured at 30 months using the PedsQL-Gastrointestinal Symptoms Scale [32]. Measures of cardiometabolic health and systemic inflammation will be made using fasting blood collected from each participant at 3 years of age.…”
Section: Methodsmentioning
confidence: 99%